Projecting the Medium-Term: Outcomes and Errors for GDP Growth - Marcus Kappler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
The focus of this paper is the evaluation of a very popular method for potential output estimation and medium-term forecasting? the production function approach?in terms of predictive performance. For this purpose, a forecast evaluation for the three to five years ahead predictions of GDP growth for the individual G7 countries is conducted. To carry out the forecast performance check a particular testing framework is derived that allows the computation of robust test statistics given the specific nature of the generated out-of sample forecasts. In addition, medium-term GDP projections from national and international institutions are examined and it is assessed whether these projections convey a reliable view about future economic developments and whether there is scope for improving their predictive content.
Keywords: C53; E27; E23; 330; Potential output; projections; forecast evaluation; Wirtschaftspotenzial; Wirtschaftsprognose; Prognoseverfahren; Bewertung; G-7-Staaten